2016
DOI: 10.5194/acp-16-4707-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interferences in photolytic NO<sub>2</sub> measurements: explanation for an apparent missing oxidant?

Abstract: Abstract. Measurement of NO 2 at low concentrations (tens of ppts) is non-trivial. A variety of techniques exist, with the conversion of NO 2 into NO followed by chemiluminescent detection of NO being prevalent. Historically this conversion has used a catalytic approach (molybdenum); however, this has been plagued with interferences. More recently, photolytic conversion based on UV-LED irradiation of a reaction cell has been used. Although this appears to be robust there have been a range of observations in lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
158
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(165 citation statements)
references
References 91 publications
5
158
1
Order By: Relevance
“…As a result, thermal decomposition of reservoir species containing NO 2 can lead to erroneously enhanced NO 2 measurements. Reed et al (2016) showed that the PAN interference could be up to 8 and 25 % when using an actively cooled and a not actively cooled photolytic converter, respectively. In the laboratory, we found NO 2 enhancements of 30 % by mixing PAN with the sample flow (at 35 • C instrument temperature and pressure level of 250 hPa), which was quantitatively generated from a NO calibration gas by photolysis of acetone (100 ppbv) in a flow system (Pätz et al, 2002;Volz-Thomas et al, 2002).…”
Section: Thermal Decomposition Of No 2 -Containing Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, thermal decomposition of reservoir species containing NO 2 can lead to erroneously enhanced NO 2 measurements. Reed et al (2016) showed that the PAN interference could be up to 8 and 25 % when using an actively cooled and a not actively cooled photolytic converter, respectively. In the laboratory, we found NO 2 enhancements of 30 % by mixing PAN with the sample flow (at 35 • C instrument temperature and pressure level of 250 hPa), which was quantitatively generated from a NO calibration gas by photolysis of acetone (100 ppbv) in a flow system (Pätz et al, 2002;Volz-Thomas et al, 2002).…”
Section: Thermal Decomposition Of No 2 -Containing Speciesmentioning
confidence: 99%
“…However, previous studies identify an unexplained imbalance between the measured and calculated NO 2 in low-NO x regions, which was explained by interferences of NO 2 -containing species and the large uncertainty of the calculations (e.g., Crawford et al, 1996;Reed et al, 2016). Thus, the impact of interference from NO 2 -containing species on the IAGOS measurements requires further investigations, which will be performed once a larger data set is available.…”
Section: Thermal Decomposition Of No 2 -Containing Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the knowledge of the spatial distribution of NO x is important to identify the sources, sinks and its partitioning between NO and NO 2 in the atmosphere (Monks et al, 2009). 10 Most relevant natural sources of NO x are lightning (LNO x ), biomass burning, soil emissions, and anthropogenic sources, such as power generation, road transportation and aviation. The current knowledge of the global distribution of NO x and its emission estimates is based mostly on specific aircraft missions (Emmons et al, 1997;Rohrer et al, 1997;Schumann and Huntrieser, 2007;Ziereis et al, 2000;Gressent et al, 2016), on surface 15 monitoring stations (Aerosols, Clouds and Trace gases Research Infrastructure (ACTRIS); www.actris.eu), satellite measurements (Fishman et al, 2008;de Laat et al, 2014;Duncan et al, 2015) and model simulations (Ehhalt et al, 1992;Emmons et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of NO 2 to NO conversion, a potential interference from NO z species cannot be fully excluded for the NO 2 measurement, e.g. (Villena et al, 2012;Reed et al, 2016). Therefore, a direct detection of NO 2 is advantageous.…”
mentioning
confidence: 99%